The effectiveness of (Suchman Inquiry Model) over personal intelligence of the third intermediate grade students in the subject of chemistry - Al-Tamimi, Ahmed Laibi Hussein (Technium Social Sciences Journal, 2023)
The research aimed to know the effectiveness of (Suchman Inquiry Model) in personal intelligence among third-grade intermediate students, and for the purpose of achieving the goal of the research, the experimental method was adopted, as a quasi-experimental design with partial control for two equal groups was used with a post-test for personal intelligence. The design was applied to (61) students, the group Experimental (30) students and control (31) students of the third intermediate grade in Al-Riyadah Secondary School for Outstanding Students of the General Directorate of Education in Baghdad Al-Karkh/3 for the academic year (2021-2022). And the formulation of behavioral objectives and the preparation of study plans, and the research relied on a tool which is the personal intelligence scale, the experiment was applied in (2021-2022), for a full academic year, the two research groups were studied by the researcher, and the two research groups were rewarded with (the chemistry degrees for the past year, and the information test The personal intelligence scale, which consisted of (50) items, was used to find honesty and reliability, the chemistry book for the third intermediate grade was selected to teach students, and after completing the experiment, analysis of the results were statistically obtained through the statistical package SPSS, and a set of results appeared on the basis of which the researcher put several recommendations as well as some suggestions.